Biofeedback pelvic floor muscle training and posterior tibial nerve electrostimulation for treatment of faecal incontinence: monotherapy versus combined therapy: a prospective randomized trial - Elsawy, Mervat Sheta (2023)
Faecal incontinence is a common anorectal medical trouble among adult population. The aim was to compare the efficacy of biofeedback pelvic floor muscle training versus posterior tibial nerve electrical stimulation versus combination of both of them in treatment of patients with faecal incontinence. The study included 71 randomly selected patients with faecal incontinence. Eleven patients had one or more exclusion criteria were excluded from the study. Sixty patients were included in the trial. They were randomly assigned to receive biofeedback pelvic floor muscle training (biofeedback group), posterior tibial nerve electrostimulation (posterior tibial nerve electrostimulation group) or combined therapy (combined group). Primary outcome measure was Wexner Faecal Continence scale. Secondary outcome measures were maximal squeezing anal pressure, maximal voluntary anal contraction time and patient global assessment of effect of faecal incontinence on quality of life. The